Integrating comprehensive genomic sequencing of non-small cell lung cancer into a public healthcare system. (2022) - Perdrizet, Kirstin; Stockley, Tracy L.; Law, Jennifer H.; Smith, Adam; Zhang, Tong; Fernandes, Roxanne; Shabir, Muqdas; Sabatini, Peter; Youssef, Nadia Al; Ishu, Christine; Li, Janice JN; Tsao, Ming-Sound; et al.
Highlights: Comprehensive gene profiling in NSCLC identified targets in 31% of cases after standard testing. In 16% of patients therapy was changed after comprehensive profiling. Comprehensive profiling after standard testing led to clinical trial enrolment in 10% of patients. Abstract: Objectives: Standard molecular testing for patients with stage IV non-small cell lung cancer (NSCLC) in the Canadian publicly funded health system includes single gene testing for EGFR, ALK, and ROS-1 . Comprehensive genomic profiling (CGP) may broaden treatment options for patients. This study examined the impact of CGP in a publicly funded health system. Methods: Consenting patients with stage IV NSCLC without known targetable alterations underwent CGP on diagnostic samples. Patients that had progressed on targeted therapy were also eligible. The CGP assay was a hybrid capture next generation sequencing (NGS) panel (Oncomine Comprehensive Assay Version 3, ThermoFisher). The number of actionable alterations, changes in treatment, clinical trial eligibility and costs as a result of CGP were evaluated and patient willingness-to-pay. Results: Of 182 screened patients, 134 (74%) had successful CGP testing. Twenty percent had received prior targeted therapy. Incremental actionable alterations were identified in 31% of patients. The most common novel targets identified were mutations in ERBB2 (exon 20 insertions), MET (exon 14 skipping) and KRAS (G12C). At data cut off (31/12/2020), 16% of patients had a change in treatment as a result of CGP. Additional clinical trial options were identified for 75% of patients. The incremental direct laboratory cost for CGP beyond public reimbursement for single gene tests was 747 CAD/case. Conclusion: CGP identifies additional actionable targets beyond single gene tests with a direct impact on patient treatment and increased clinical trial eligibility. These benefits highlight the value of CGP in patients with NSCLC in public health systems.